How a multidisciplinary 'One Health' approach can combat the tick-borne pathogen threat in Europe. (May 2015) - Vayssier-Taussat, Muriel; Cosson, Jean François; Degeilh, Brigitte; Eloit, Marc; Fontanet, Antoine; Moutailler, Sara; Raoult, Didier; Sellal, Eric; Ungeheuer, Marie-Noelle; Zylbermann, Patrick
ABSTRACT : In Europe, ticks are the major arthropod vectors of disease agents to humans and domestic animals. They are capable of transmitting many pathogens most of which have been discovered or identified as tick-borne pathogens in the last 20 years. In recent years, unexplained syndromes occurring after a tick bite have become an increasingly important issue in public and animal health. Ticks and wildlife (the main reservoir of tick-borne pathogens) are highly susceptible to global environmental and socio-economic changes, which in turn may lead to an increased burden of tick-borne diseases. In this review, we explain the importance of a 'One Health' approach to better combat tick-borne diseases.